The Size and Localization of Ribeye and GluR2 in the Auditory Inner Hair Cell Synapse of C57BL/6 Mice Are Affected by Short-Pulse Corticosterone in a Sex-Dependent Manner - Ewa Domarecka; Heidi Olze; Agnieszka J. Szczepek (Brain Sciences)
Background: Inner hair cell (IHC) ribbon synapses are the initial synapses in the auditory pathway, comprising presynaptic ribbons and postsynaptic glutamate receptors on the peripheral afferent fibers. The excitatory neurotransmitter glutamate primarily signals through AMPA-type heterotetrameric receptors (AMPARs), composed of GluR1, GluR2, GluR3, and GluR4 subunits. Research shows that corticosterone affects AMPA receptor subunits in the central nervous system. The present study investigates the effects of corticosterone on AMPA receptor subunits in the murine cochlea. Methods: Cochlear explants were isolated from male and female C57BL/6 pups (postnatal days 4–5), treated for 20 min with 100 nM corticosterone, and cultured for an additional 24 h. The concentration of AMPAR protein subunits was quantified using an ELISA assay, while gene expression was analyzed using RT-PCR. The synaptic localization patterns of GluR2 and Ribeye were examined using immunofluorescence and confocal microscopy. Results: Male C57BL/6 mice have a significantly greater basal concentration of the GluR2 subunit than females and more GluR2 puncta per IHC than females. Corticosterone increases the size of Ribeye in males and increases twofold GluR2/Ribeye colocalization in the apical region of females. Conclusions: Exposure of membranous cochleae to corticosterone induces changes consistent with neuroplasticity in the auditory periphery. The observed effect is sex-dependent.